2020
DOI: 10.1016/j.ijheatfluidflow.2019.108516
|View full text |Cite
|
Sign up to set email alerts
|

Wall jet similarity of impinging planar underexpanded jets

Abstract: Velocity profiles and wall shear stress values in the wall jet region of planar underexpanded impinging jets are parameterized based on nozzle parameters (stand-off height, jet hydraulic diameter, and nozzle pressure ratio). Computational fluid dynamics is used to calculate the velocity fields of impinging jets with height-to-diameter ratios in the range of 15 to 30 and nozzle pressure ratio in the range of 1.2 to 3.0. The wall jet has an incomplete self-similar profile with a typical triple-layer structure as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Guo et al [23] identified that the confinement of an impinging jet has no significant effect on the velocity decay rate, and the presence of the upper confinement plate accelerates the wall jet growth rates compared to those reported in the previous plane and radial wall jet experiments. However, the numerical study results of radial wall jet by Fillingham and Novosselov [24] exhibited an excellent agreement with those of plane wall jet reported by Naqavi et al [11] in terms of the evolution of both length and velocity scales. Bagherzadeh et al [2] reported that wall roughness influences the decay rate.…”
Section: Introductionsupporting
confidence: 79%
“…Guo et al [23] identified that the confinement of an impinging jet has no significant effect on the velocity decay rate, and the presence of the upper confinement plate accelerates the wall jet growth rates compared to those reported in the previous plane and radial wall jet experiments. However, the numerical study results of radial wall jet by Fillingham and Novosselov [24] exhibited an excellent agreement with those of plane wall jet reported by Naqavi et al [11] in terms of the evolution of both length and velocity scales. Bagherzadeh et al [2] reported that wall roughness influences the decay rate.…”
Section: Introductionsupporting
confidence: 79%
“…The velocity profiles were not measured for x < 10 mm due of likely probe interaction with the plasma zone (plasma length ∼7 mm). The flow is accelerated in the plasma discharge region [76] and as the wall jet propagates downstream, the velocity profile flattens due to viscous losses, momentum displacement [44] and specific to the EHD scenario, due to space charge effects. This jet-like expansion from the active electrode has been shown in similar pitot-tube experiments and the PIV experiments and some have modeled DBD actuators using wall-jet similarity [25,44,45].…”
Section: Velocity Characteristicsmentioning
confidence: 99%
“…Considering 2D geometry, the volume of ionization can be calculated from length and height measurements. The size and the charge density in the ionization zone can be considered analogous to virtual origin parameters in the wall jet literature [40][41][42]. DBD wall similarity analysis was recently proposed [43]; however, additional experimental data is needed to perform robust non-dimensional analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The constriction bends to form an impinging jet on the upper surface of each baffle (Figure ). The behavior of impinging jets has been described in the literature, and their comprehensive analysis is beyond the scope of this paper. However, for the purpose of this work, it is important to understand that the angled impinging jets create stagnation regions (Figure Ai, left).…”
Section: Resultsmentioning
confidence: 99%